ANALYSIS OF THEORETICAL SOURCES ON SUFISM IN MODERN SOCIETY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article analyzes religious-philosophical views about the role and importance of blame in modern society .